2018
DOI: 10.3390/nu10070897
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Food Neophobia Level on Fruit and Vegetable Intake and Its Association with Urban Area of Residence and Physical Activity in a Nationwide Case-Control Study of Polish Adolescents

Abstract: Among the factors that may influence fruit and vegetable intake, there is a food neophobia level, but the other elements, including physical activity and place of residence, must also be taken into account as interfering ones. The aim of the study was to analyze the association between food neophobia level and the intake of fruits and vegetables in a nationwide case-control study of Polish adolescents (12–13 years), including the influence of gender, the physical activity program participation and the place of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 53 publications
4
29
0
Order By: Relevance
“…Most of the significant associations were negative, that is, greater FN precludes lower intake. Our findings parallel the results of other studies that associated FN with lower intake of fruits and vegetables 14‐16, 18, 19, 37 . In contrast, a positive association was observed between FN and the consumption of codfish.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of the significant associations were negative, that is, greater FN precludes lower intake. Our findings parallel the results of other studies that associated FN with lower intake of fruits and vegetables 14‐16, 18, 19, 37 . In contrast, a positive association was observed between FN and the consumption of codfish.…”
Section: Discussionsupporting
confidence: 91%
“…Studies suggest that FN has adverse impacts on food choices affecting the quality and variety of the diet 3, 12 . This trait was previously associated with higher consumption of unhealthy foods, a lower consumption of fruit, vegetables and fish and with poorer overall dietary quality 5‐19 . Increasingly neophobia is negatively associated with pleasantness of food and with a higher dislike of food overall 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This need is associated with the fact that at-home exposure of children results not only in higher preferences but also higher intake—both at home and at school lunch [38]. In a Polish nationwide sample, an association between higher fruit and vegetable intake, higher variety of product exposure, lower food neophobia level, more frequent socializing with peers, and more frequent physical activity confirmed that all of these factors aid in the development of proper nutritional habits [39]. Therefore, mothers must be educated about the need for exposure, as nutritional knowledge of parents is indicated to be crucial for influencing the fruit and vegetable consumption of their children [40].…”
Section: Discussionmentioning
confidence: 99%
“…The #goathletics Study aimed to evaluate the effectiveness of the Athletics for All program, not only by the assessment of anthropometric measurements, but also by the assessment of physical performance and nutritional behavior [25]. For this study, the study groups were recruited following a two-stage recruitment procedure, in which adolescents aged 12–13 from all the regions of Poland (central, north, north-west, south-west, south, east) were included.…”
Section: Methodsmentioning
confidence: 99%